Colloidosome-templated poly (L-lactic acid) crystalsomes. (December 2022) - Staub, Mark C.; Yu, Shichen; Li, Christopher Y.
Abstract: Polymers have been utilized to direct nanoparticle (NP) assembly into complex shapes and morphologies. Strategies for polymer-directed NP assembly often involve tuning the phase behavior of multi-component polymer/nanoparticle systems. In this work, we report the co-assembly of polymer and NPs into hollow vesicles using confined polymer crystallization-directed assembly. 5 nm and 20 nm Fe3 O4 NPs are used as the solid surfactants to create Pickering emulsions of water and poly(L-lactic acid) (PLLA) toluene solution. The oil/water interface of the emulsion droplets templates the growth of PLLA crystals, which in turn, immobilize NPs onto the crystal surface, leading to the formation of colloido-polymer-crystalsomes (CPCs). The structure, morphology, and formation mechanism of the CPCs are investigated using electron microscopy and thermal analysis techniques. This work provides a new approach to fabricate nanoscale complex NP-polymer conjugates. Graphic abstract: Image, graphical abstract